Radiocarbon dating : avoiding errors by avoiding mixed samples - Ashmore, P. J.
Chronology and its refinement continues to be important, especially in the methods by which the dates are actually achieved. Here, the question of whether single object/bone samples provide more accurate dates than mixed samples is debated, and applied to samples from prehistoric Scotland.